Planning of electric vehicle fast-charging station based on POI interest point division, functional area, and multiple temporal and spatial characteristics. (November 2022) - Bian, Haihong; Zhou, Chengang; Guo, Zhengyang; Wang, Ximeng; He, Ying; Peng, Shan
Abstract: There are some problems with the fast-charging station of urban electric vehicles (EV), including blind construction, unreasonable planning location, and neglect of user requirements. This paper presents a planning method considering functional zoning and traffic influencing factors. Firstly, the planning area's POI points and road network information are processed based on the geographic information software ArcGIS, and the urban functional zoning is divided. Then, two factors that affect the user's time-consuming cost are studied, such as regional traffic congestion and signal waiting time. Secondly, according to the initial location of the user, the road network adjacency matrix, and the probability function of the user selecting the fast-charging station, the Floyd algorithm is used to calculate the time-consuming cost of the user to the fast-charging station. In order to reflect the profitability of the fast-charging station, the payback period function is also introduced. Finally, the MOSAPSO algorithm is used to solve the multi-objective function composed of the investment cost, operation, and maintenance cost, payback period, and user time-consuming cost of the fast-charging station. The optimized site selection and management layout of fast charging stations provide a certain reference for urban EV fast charging stations.